Navigating the diagnostic challenges of myoclonus in neurodegenerative disorders: video-EEG/polygraphy, clinical vignettes, and narrative analysis - d’Orsi, Giuseppe; Di Claudio, Maria Teresa; Soccio, Assunta Anna; Palumbo, Valentina; Ferro, Carmela Pia; Costantino, Umberto; Latino, Raffaella; Fogli, Danilo (Frontiers in Neurology, 2025)
PurposeMyoclonus—sudden, brief, involuntary muscle jerks—is a frequent and diagnostically challenging feature across neurodegenerative disorders. Unlike epileptic myoclonus, these manifestations rarely involve seizures; they often reflect extensive multisystemic pathology (cortical, subcortical, peripheral). Distinguishing neurodegenerative myoclonus from other movement disorders and pinpointing its origin is crucial for accurate diagnosis, prognosis, and tailored management. This narrative analysis explores the diverse phenomenology of myoclonus in neurodegenerative conditions, emphasizing how presentations often differ from typical epileptic myoclonus, which necessitates a nuanced diagnostic approach. We also highlight the indispensable role of video-electroencephalography (video-EEG) with polygraphy in this context.MethodsWe synthesized existing literature on myoclonus in neurodegenerative disorders, complemented by illustrative clinical vignettes. The diagnostic utility of video-EEG with polygraphy was critically examined, focusing on its capacity to integrate motor behavior analysis with concurrent EEG and electromyographic (EMG) activity.ResultsMyoclonus in neurodegenerative conditions (e.g., dementias, basal ganglia degenerations, spinocerebellar degenerations) presents with diverse phenomenology, often differing significantly from typical epileptic myoclonus. Video-EEG/polygraphy emerged as the gold standard, enabling precise characterization (focal, multifocal, generalized, rhythmicity, triggers) and localization of origin. Its adaptable protocols are fundamental for capturing the fluctuating, context-dependent nature of myoclonus in these progressive conditions, and for distinguishing pathological cortical excitability from subcortical or spinal origins.ConclusionVideo-EEG/polygraphy provides objective, real-time insights into the complex interplay of brain and muscle activity, profoundly refining our understanding of neurodegenerative myoclonus. This guides accurate differential diagnosis and informs effective patient care, proving essential for optimal patient management and prognosis in these challenging conditions.